(untitled) (Sinología hispánica. China Studies Review, 2020)
City image communication is of high significance for city marketing and city competitiveness enhancement. The article explores the interaction between news discourse and Nanjing city image communication. Literature review: Most of studies focus on city architecture, tourism and landscapes and public security. However, less attention has been paid to the relations between discourse and city image communication. Research questions: 1. Who is speaking to communicate Nanjing city image? 2. What kind of image of Nanjing is communicated? 3. How or in what way is Nanjing city image communicated? Methodology: The study adopts a fusion of the perspectives of constructivism and cultural discourse studies (CDS) to account for Nanjing city image communication in political and cultural contexts of contemporary China. Results: (1) the voices of ordinary professionals and citizens in the news narration reflect the trend of diversity in discourse subjects;(2) Nanjing city image are constructed from four aspects, governing style, economic development, environmental protection, history, culture & education, with the negative topic of corruption, bribery and air/water pollution; (3) Nanjing city image are communicated favorably by news stories of event profiles and general picture profiles, giving us a portrait of Nanjing mostly by describing hot issues and introducing policies. Conclusions: The media discourse of Nanjing city image is a reflection of social changes and realities, working as a catalyst to shape people’s views toward Nanjing’s reality and to mold the practice of the communication. The study contributes to city image communication by developing an interdisciplinary discursive framework and provides Implications for city administrators and communicative strategists, professionals in city marketing and professional communication theorist in constructing and communicating city image.